Herbal therapy in Oral Submucous Fibrosis: A Short Review - Sanjay C J; Shilpa Padar Shastry; Karthikeya Patil; Nagabhushana Doggalli; Naveen Kumar; Swathi Sharma (Institute of Medico-legal Publications Pvt Ltd, 2021)
Oral submucous fibrosis (OSMF) is a potentially malignant disorder causing significant mortality andmorbidity. It is a chronic insidious disease, which progressively causes reduced mouth opening, stiffnessof oral mucosa and inability to eat. Treatment of this condition is difficult as various modalities have beenused, but with its own limitations and inefficiency. Reversing the fibrosis and improving the mouth openingremains the most challenging part of the management. In recent years, various studies have been conductedon usage of alternative modalities for the management of OSMF. These include several herbal products likealoevera, turmeric, spirulina, Oxitard, Tulsi, nigella sativa, turmeric with black pepper and many others.The objective of this article is to review various herbal agents that has been used in the treatment of OSMF.